2014
DOI: 10.1103/physrevb.89.195428
|View full text |Cite
|
Sign up to set email alerts
|

Anderson localization at the subwavelength scale for surface plasmon polaritons in disordered arrays of metallic nanowires

Abstract: Using one-and two-dimensional random arrays of coupled metallic nanowires as a generic example of disordered plasmonic systems, we demonstrate that the structural disorder induces localization of light in these nanostructures at a deep-subwavelength scale. The ab initio analysis is based on solving the complete set of three-dimensional Maxwell equations. We find that random variations of the radius of coupled plasmonic nanowires are sufficient to induce the Anderson localization (AL) of surface plasmon polarit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…[42] We further proceed to simulate a random network of AgNWs with different areal densities (ρ NW ) to investigate the optimum value of ρ NW for the strongest E-field in the UCNPs monolayer, G(ρ NW ), considering the node effects ( Figure S5a, Supporting Information). From the comparison, we found that the former is greater than the simple summation value by 2.89 times, and this indicated that the node-induced effects contribute to the field enhancement by about three times in the random network.…”
Section: Resultsmentioning
confidence: 99%
“…[42] We further proceed to simulate a random network of AgNWs with different areal densities (ρ NW ) to investigate the optimum value of ρ NW for the strongest E-field in the UCNPs monolayer, G(ρ NW ), considering the node effects ( Figure S5a, Supporting Information). From the comparison, we found that the former is greater than the simple summation value by 2.89 times, and this indicated that the node-induced effects contribute to the field enhancement by about three times in the random network.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated E ‐field spectra, E ( λ ), for the DANPs case exhibits several peaks in optical and NIR range as well as higher intensity than E mc ( λ ) or E ( λ ,〈 q 〉) (Figure d). These data would suggest that the E ‐field enhancement in the DANPs over OANPs can be linked to Anderson localization (AL) of surface plasmons by which strong near field formation around the hot spots in disordered metal NPs array is expected . Indeed, the dependences of the squared E ‐field and Abs spectra on d are strongly correlated (Figure S7, Supporting Information), which indicates that the E ‐field concentration in the IUI layer is mainly intervened by the Vis–NIR absorption in DANPs in the MIUIM.…”
mentioning
confidence: 93%
“…Another reason more possibly behind the stronger E ‐field in DANPs over OANPs would originate from the better localized near field. The stronger localization of plasmon is induced by multiple subwavelength coherent scattering and interference in DANPs which is expected from the AL in the disordered media in which plasmonic correlation length is smaller than incidnet wavelength . By the AL, electromagnetic energy is expected to be accumulated in hot spots associated with localized surface plasmon, and subsequently, induce stronger E ‐field enhancement in DANPs.…”
mentioning
confidence: 99%
“…A particularly important manifestation of this effect is the transverse Anderson localization [22] that can be achieved in optical lattices disordered only in the transverse direction, but not in the direction of light propagation, similarly to the time-independent potentials considered in [13,14]. Transverse Anderson localization has been reported in optically induced lattices [24], fabricated [25] and laser-written [26] waveguide arrays, and in plasmonic nanowires [29], to name just a few settings. Inclusion of transverse disorder suppresses Bloch oscillations in lattices with transverse gradients [31] and even prevents resonant delocalization in such structures if the coupling constants are longitudinally modulated [32].…”
Section: Introductionmentioning
confidence: 91%
“…This is universal phenomenon that may occur for waves of different physical nature, since it is caused by the localization of eigenmodes of the disordered potential in one-and two-dimensional settings [15]. Anderson localization has been observed with microwaves [16,17], matter [18,19] and acoustic [20] waves, and in disordered optical lattices [21][22][23][24][25][26][27][28][29][30]. A particularly important manifestation of this effect is the transverse Anderson localization [22] that can be achieved in optical lattices disordered only in the transverse direction, but not in the direction of light propagation, similarly to the time-independent potentials considered in [13,14].…”
Section: Introductionmentioning
confidence: 99%